If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 5) + -58 = 18 Reorder the terms: 7(5 + x) + -58 = 18 (5 * 7 + x * 7) + -58 = 18 (35 + 7x) + -58 = 18 Reorder the terms: 35 + -58 + 7x = 18 Combine like terms: 35 + -58 = -23 -23 + 7x = 18 Solving -23 + 7x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 7x = 18 + 23 Combine like terms: -23 + 23 = 0 0 + 7x = 18 + 23 7x = 18 + 23 Combine like terms: 18 + 23 = 41 7x = 41 Divide each side by '7'. x = 5.857142857 Simplifying x = 5.857142857
| 2x+24=-8-4(2x-8) | | 5e=55 | | 5.9=-A-4.8 | | 2k+3-k=k+2 | | -9=1-6x+2 | | -10/2(-5)= | | 9r=-6 | | x+6=8x-15 | | 7-3x-10=-66 | | -1/6*b=3 | | 4k+3=10-3k | | -3(y+2)=-2(y+4)-y | | -3x^2=1 | | (19x+6)(20x)= | | 0=3x^2+1 | | 5m^2+13m+15=0 | | f(x)=5x^2+10x+1 | | x^3-5x^2-5x-1=0 | | 3y-9y+5w+w= | | c/4+3=8 | | 5-1k=21-3k+12 | | (51x+3)(1+52x)= | | X/8-6=8 | | 5+x/8=-3 | | (x+2x^3-3)/(x-1)=0 | | .5x+16(x+2)=48.5 | | 5x-11=10+12x | | (x+2x^3-3)/(x-1) | | x^4-9x^2-52=0 | | 3+y=19 | | 2z-3-2(1+z)=-5 | | Y=-2/5 |